Predictors of in-hospital mortality in patients with acute ischemic stroke treated with thrombolytic therapy - Heuschmann, Peter U.; Kolominsky-Rabas, Peter; Röther, Joachim; Misselwitz, Björn; Lowitzsch, Klaus; Heidrich, Jan; Hermanek, Peter; Leffmann, Carsten; Sitzer, Matthias; Biegler, Marcel; Buecker-Nott, Hans Joachim; Berger, Klaus (Journal of the American Medical Association, 2004)
Context: Data are limited regarding the risks and benefits of thrombolytic therapy for acute ischemic stroke outside of clinical trials. Objective: To investigate predictors of in-hospital mortality in patients with ischemic stroke treated with intravenous tissue plasminogen activator (tPA) within a pooled analysis of large German stroke registers. Design and Setting: Prospective, observational cohort study conducted at 225 community and academic hospitals throughout Germany cooperating within the German Stroke Registers Study Group. Patients: A total of 1658 patients with acute ischemic stroke who were admitted to study hospitals between 2000 and 2002 and were treated with tPA. Main Outcome Measure: In-hospital mortality. Results: One hundred sixty-six patients (10%) who received tPA died during hospitalization, with 67.5% of these deaths occurring within 7 days. Factors predicting in-hospital death after tPA use were older age (for each 10-year increment in age, adjusted odds ratio [OR], 1.6; 95% confidence interval [CI], 1.3-1.9) and altered level of consciousness (adjusted OR, 3.4; 95% CI, 2.4-4.7). The overall rate of symptomatic intracranial hemorrhage was 7.1% and increased with age. One or more serious complications was observed in 27.2% of all patients and in 83.9% of patients who died after tPA treatment. An inverse relation between the number of patients treated with tPA in the respective hospital and the risk of in-hospital death was observed (adjusted OR, 0.97; 95% CI, 0.96-0.99 for each additional patient treated with tPA per year). Conclusion: In patients with ischemic stroke who are treated with tPA, disturbances of consciousness and increasing age are associated with increased in-hospital mortality.
Created from Fastlane, Scopus look-up